Plasma granulysin levels and cellular interferon-γ production correlate with curative host responses in tuberculosis, while plasma interferon-γ levels correlate with tuberculosis disease activity in adults - Sahiratmadja, E.; Alisjahbana, B.; Buccheri, S.; Di Liberto, D.; de Boer, T.; Adnan, I.; van Crevel, R.; Klein, M.R.; van Meijgaarden, K.E.; Nelwan, R.H.H.; van de Vosse, E.; Dieli, F.; et al. (Tuberculosis (Edinburgh, Scotland), 2007)
Granulysin is a recently identified cytolytic protein which is expressed by human cytotoxic T-lymphocytes and natural killer (NK)-cells, and has broad antimicrobial and tumoricidal activity. Circulating granulysin levels are associated with T- and NK-cell activity, and may thus reflect protection-associated cellular immune responses. In a case-control study in Indonesia, a highly tuberculosis (TB)-endemic country, we therefore determined plasma granulysin levels in adults with active pulmonary TB before, during, and after TB treatment, both in mild/moderate-TB and advanced-TB patients, and compared these to healthy neighbourhood controls. Adults with active pulmonary TB had significantly lower plasma granulysin levels compared to controls. After 2 months of anti-TB therapy, levels in TB patients had significantly increased, reaching values similar to those in controls. Plasma granulysin levels further increased after completion of TB therapy, being significantly higher than those in controls. Plasma granulysin levels correlated inversely with TB disease activity but not with TB disease severity. In contrast, plasma interferon-γ (IFN-γ) levels were significantly higher in active TB cases than in controls, normalised during treatment and correlated with both TB disease activity and TB disease severity. At the cellular level, granulysin and IFN-γ expression both correlated inversely with disease activity. Interestingly, granulysin was predominantly expressed by IFN-γ negative T-cells, suggesting that the cellular sources of IFN-γ and granulysin in TB are partly non-overlapping. The observation that plasma granulysin levels and cellular IFN-γ production correlate with curative host responses in pulmonary tuberculosis points to a potentially important role of granulysin, next to IFN-γ, in host defence against M. tuberculosis.